How Supply Chain Mediates the Relationship between HRM Practices and Employee Performance? - Komala Lenda (International Journal of Supply Chain Management, 2020)
The basic goal of the present study is to examine the role of HR practices such as compensation, training and empowerment on the employee performance of public sector companies in Indonesia. The second aim of the ongoing study is to the investigation of the mediating role of supply chain management integration among the links of compensation, training, empowerment and employee performance of public sector companies in Indonesia. The questionnaire method has been adopted by the study to collect the data from the respondents while PLS-SEM has been employed for the data analysis. The results indicated that training and empowerment have a positive and significant link with the employee performance of the public sector organizations. The results also exposed that supply chain management integration significantly mediates among the links of HR practices such as compensation, training, empowerment and employee performance of public sector companies in Indonesia. These findings are suitable for the regulation development authorities along with upcoming researchers in terms of making regulation and future investigation related to HR practices, supply chain management and employee performance.